DETERMINASI KEPUTUSAN HEDGING PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Megawati, Ida Ayu Putu; Wiagustini, Luh Putu; Sri Artini, Luh Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.10.TAHUN 2016, 2016)
Companies should to manage all facing risks in order to achieve the company’s goal to maximize their value. One tool to manage the risk is hedging with derivative instruments. This study purposed to determine the significant influence of leverage, company size, profitability and liquidity on the manufacturing company's hedging decision. The research samples were 114 manufacturing companies. The data obtained from the publication of manufacturing company`s annual financial statements and report by the Indonesia Stock Exchange. The data was analysed with the logistic regression analysis. The statistical tests analysis found that leverage has a positive and not significant effect on the hedging decision, company size and profitability has a positif and significant effect on the hedging decision, and the liquidity has a negative and significant effect on the hedging decision.
Keywords: Leverage, Firm Size, Profitability, Liquidity, Risk Management.